Design of the exercise MRI evaluation of HIV-pulmonary arterial hypertension longitudinal determinants (EXALTED) trial. Issue 11 (November 2017) - Alaiti, Mohamad Amer; Goud, Aditya; Ramani, Gautam; Bagchi, Sashwatee; Al-Kindi, Sadeer; Sawicki, Steven; Longenecker, Christopher; Jenkins, Trevor; Pauza, David; Park, Myung; McComsey, Grace; Simonetti, Orlando; et al.
Abstract : Background: Pulmonary arterial hypertension (PAH) is a potentially serious cause of dyspnea and exercise limitation in patients with HIV infection. In this trial, we propose using exercise MRI in conjunction with cardiopulmonary testing to delineate PAH from other causes of cardiovascular dysfunction, identify individuals with exercise-induced PAH who are at high risk of developing resting PAH, and provide longitudinal estimates of progression of PAH and right ventricular function. Methods: In this prospective observational study, HIV patients with dyspnea and exercise limitation in the absence of identifiable causes and those who meet the inclusion criteria will be enrolled based on resting pulmonary artery pressure (⩽ or >40 mmHg) on a screening echocardiogram and exercise limitation on the Modified Medical Research Council dyspnea scale. Patients without evidence of resting PAH will be enrolled into both rest and exercise MRI and cardiopulmonary testing protocol, whereas patients with evidence of PAH on resting echocardiograms will undergo only resting cardiac MRI studies to evaluate right ventricular function and fibrosis. Both patient subgroups will be followed for 24 months to obtain longitudinal progression of the disease. In a sub-study, we will further analyze inflammatory variables that may predict these changes, thus allowing early identification of these patients. Implications and conclusions: This trial will be the first study to provide an understanding of the mechanisms underpinning the functional deterioration of the right ventricle in patients with HIV and will impart insight into the immune mediators of PAH progression and right ventricular functional deterioration in patients with HIV-PAH. Abstract : Supplemental Digital Content is available in the text